Fragmentasi Umat dan Penciptaan Otoritas Keagamaan: Tanggapan terhadap ‘Islam Lokal’ dan ‘Islam Asing’ di Indonesia - Pribadi, Yanwar (Jurnal Masyarakat dan Budaya, 2019)
Today, Islamist groups in Indonesia are apprehensive with Islam Nusantara, a catch-all term to refer to various expressions of localised Islam and socio-political thoughts and attitudes propagated by the country?s largest Muslim organisation, the Nahdlatul Ulama (NU). In response, the proponents of Islam Nusantara call for the unity of Indonesian Muslims to restrain what they perceive as an orchestrated effort to Arabize Indonesian Islam and eradicate local cultures and traditions. By looking at Banten and Madura through ethnographic fieldworks in between 2009-2018, this paper investigates the contestation between supporters of ?local? and ?foreign? Islam in defining their own Islam and making religious authority. While both supporters share the global viewpoints of Sunni Islam, the former is strongly characterised by local cultures and traditions that have been well preserved for centuries. The latter is well-known to display foreign-influenced, mostly Salafism from Gulf countries, expressions of Islam that include communal piety, religious commodification, Islamic populism, and popular Islamism. I argue that in both contemporary Banten and Madura, the defining of Islam and the making of religious authority have been frequently marked by conflicting responses in complex and fluctuated relationships. The relationships involve the phenomena of contestation between variants of Indonesian Islam and the fragmentation of the ummah.